Metabolic Syndrome in Adults with Nonalcoholic Fatty Liver Disease (Journal of Renal and Hepatic Disorders, 2021)
Nonalcoholic fatty liver disease (NAFLD) is associated with insulin resistance, obesity, and other features of metabolic syndrome. It is identified as the most common cause of liver enzyme derangement. Lately, NAFLD has generated interest in exploring treatment options, including weight loss and dietary interventions. An association of NAFLD with metabolic syndrome has been suggested in contemporary literature. In this study, we attempted to look into the association of NAFLD with metabolic syndrome. In this study, 80 adult NAFLD patients were recruited from a tertiary care hospital. Among these, 42 were males and 38 females with a mean age of 44.46±13.146 years (range 18–82 years). Grades of fatty liver and presence or absence of metabolic syndrome were studied in this patient population. Patients who did not qualify for the criteria of metabolic syndrome were placed in Group 1 and those who fulfilled the stated criteria were considered in Group 2. There were 29 (36.25%) patients in Group 1 and 51 (63.75%) in Group 2. All the patients in Group 1 were having Grade I fatty liver whereas patients in Group 2 were found to having varying grades of fatty liver, with six patients having Grade III fatty liver. We found statistically significant difference in various parameters of study (liver enzymes, high-density lipoprotein (HDL), triglycerides, and blood pressure) between Group 1 and Group 2. Ultrasound evidence of a fatty liver should be considered as a predictor of metabolic syndrome, and these patients must be investigated for the different components of metabolic syndrome so as to have early diagnosis and intervention to alter development of long-term metabolic disorders and their inherent complications.
Keywords: fatty liver; metabolic syndrome; NAFLD